Production Performance of Local Village Chicken Fed by Agriculture by-product Supplemented with Herbal Probiotics and Mud Clams Extract (Polymesoda erosa) in Kendari-South-East Sulawesi - T. Saili; R. Aka; F. A. Auza; W. L. Salido; A. M. Sari; A. Napirah (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2019)
Ninety head day old chick (DOC) of local village chicken was used in this experiment to evaluate the effect of agricultural by product-based feed supplemented with herbal probiotics (HP) and mud clams extract (MC) on production performance of local village chicken. A completely randomized design was used with 5 treatments and 4 replications. The treatments consisted of control (R0), 0.75%HP+1.5%MC (R1), 1.5%HP+3%MC (R2), 2.25%HP+4.5%MC (R3), and 3.0%HP+6.0%MC (R4). All chicken was kept in a group of five flocks equipped with feeding and water supply apparatus. The results showed that local village chicken got R2 treatment gave a significantly higher response in feed consumption (32.5gd-1) compared to R0 (23.1gd-1), R1 (23.9gd-1), R3 (24.0gd-1), and R4 (21.3gd-1). The daily gain of local village chicken was also significantly higher in R2 treatment (7.4g-1) compared to R0 (4.6gd-1), R1 (4.9gd-1), R3 (4.6gd-1), and R4 treatment (4.1gd-1). However, feed conversion resulted from those treatments did not show a significant difference. The lower feed conversion gain in this experiment has existed in R2 treatment (4.0) followed by treatment R1 (4.9), R0 (5.0), R4 (5.2), and treatment R3 (5.4). Therefore, it was concluded that the treatments had a significant effect on feed consumption and daily gain but had no effect on feed conversion of local village chicken. The inclusion level of 1.5% herbal probiotics and 3% mud clams extract gave better effect on both feed consumption and daily gain of local village chicken.